Eksplorasi Etnomatematika Makanan Tradisional Rengginang Sebagai Media Belajar Matematika - Lestari, Devi Tri; Rakhmawati, Fibri (Media Pendidikan Matematika, 2025)
Ethnomathematics is an approach that connects mathematical concepts with cultural contexts. This study aims to explore the ethnomathematics contained in the process of making traditional rengginang food and how it can be used as an effective medium for learning mathematics. Rengginang, as one of Indonesia’s traditional foods, has great potential to be integrated into mathematics learning through a manufacturing process that involves various mathematical concepts. The research method used is qualitative with an ethnographic approach, which includes observation, interviews, and documentation. The results of the study show that each stage in making Rengginang, from soaking sticky rice to frying, contains relevant mathematical concepts, such as number operations, social arithmetic, counting, comparison, geometry and time measurement. This study concludes that the process of making rengginang contains various mathematical concepts that are indirectly applied by the community. This finding shows that mathematical values can be found in traditional cultural practices, proving that ethnomathematics is an effective approach to linking local wisdom and mathematics education. Through an ethnomathematics approach, the tradition of making rengginang can not only be seen as a culture, but also as a learning medium that can help understand mathematics in a more realistic andÂ life-likeÂ way